2021
DOI: 10.1101/2021.10.15.464517
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Astrocytic urea cycle detoxifies Aβ-derived ammonia while impairing memory in Alzheimer’s disease

Abstract: Alzheimers disease (AD) is one of the foremost neurodegenerative diseases, characterized by beta-amyloid (Aβ) plaques and significant progressive memory loss. In AD, astrocytes are known to take up and clear Aβ plaques. However, how Aβ induces pathogenesis and memory impairment in AD remains elusive. We report that normal astrocytes show non-cyclic urea metabolism, whereas Aβ-treated astrocytes show switched-on urea cycle with upregulated enzymes and accumulated entering-metabolite aspartate, starting-substrat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 37 publications
2
7
0
Order By: Relevance
“…In our previous studies, we have demonstrated how common molecular pathways such as MAOB-dependent putrescine degradation and GABA production are shared, even though the triggering factors are different ( Chun and Lee, 2018 ; Chun et al, 2020 ; Heo et al, 2020 ; Jo et al, 2014 ; Nam et al, 2020 ; Pandit et al, 2020 ; Shim et al, 2019 ). We have reported that autophagic degradation pathway is commonly triggered by pathogenic molecules such as diphtheria toxin, Aβ, cytokines, damaged tissue debris, and viral infections, which usually accompany neuroinflammation ( Chun et al, 2020 ; Ju et al, 2021 ). Under pathological conditions, astrocytes take up or internalize these toxic molecules to degrade them and subsequently turn on the urea cycle to convert the accumulating toxic ammonia to less toxic urea ( Cohen, 1981 ; Ju et al, 2021 ; Meijer et al, 1990 ; Morris, 2002 ).…”
Section: Causes Of Reactive Astrocytesmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous studies, we have demonstrated how common molecular pathways such as MAOB-dependent putrescine degradation and GABA production are shared, even though the triggering factors are different ( Chun and Lee, 2018 ; Chun et al, 2020 ; Heo et al, 2020 ; Jo et al, 2014 ; Nam et al, 2020 ; Pandit et al, 2020 ; Shim et al, 2019 ). We have reported that autophagic degradation pathway is commonly triggered by pathogenic molecules such as diphtheria toxin, Aβ, cytokines, damaged tissue debris, and viral infections, which usually accompany neuroinflammation ( Chun et al, 2020 ; Ju et al, 2021 ). Under pathological conditions, astrocytes take up or internalize these toxic molecules to degrade them and subsequently turn on the urea cycle to convert the accumulating toxic ammonia to less toxic urea ( Cohen, 1981 ; Ju et al, 2021 ; Meijer et al, 1990 ; Morris, 2002 ).…”
Section: Causes Of Reactive Astrocytesmentioning
confidence: 99%
“…We have reported that autophagic degradation pathway is commonly triggered by pathogenic molecules such as diphtheria toxin, Aβ, cytokines, damaged tissue debris, and viral infections, which usually accompany neuroinflammation ( Chun et al, 2020 ; Ju et al, 2021 ). Under pathological conditions, astrocytes take up or internalize these toxic molecules to degrade them and subsequently turn on the urea cycle to convert the accumulating toxic ammonia to less toxic urea ( Cohen, 1981 ; Ju et al, 2021 ; Meijer et al, 1990 ; Morris, 2002 ). The net consequence of this degradation and turning-on of the urea cycle is the production of putrescine, which further turns on MAOB-dependent production of GABA ( Ju et al, 2021 ).…”
Section: Causes Of Reactive Astrocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently demonstrated that putrescine, the source of astrocytic GABA, is increased via the urea cycle and polyamine metabolism in reactive astrocytes (Ju, 2021). To test whether acetate alone is associated with the urea cycle and polyamine metabolism, we measured the mRNA level of carbamoyl phosphate synthetase 1 (CPS1), the first enzyme of the urea cycle, and ornithine decarboxylase 1 (ODC1), the key enzyme behind polyamine biosynthesis converting ornithine into putrescine.…”
Section: Excessive Acetate From High-grade Glioma Is Taken Up To Caus...mentioning
confidence: 99%
“…Recently, it has been shown that severely reactive astrocytes exhibit neurotoxicity by generating H 2 O 2 through the monoamine oxidase B (MAOB) is an enzyme involved in the production of GABA in astrocytes. GABA released from reactive astrocytes affects nearby neurons, and increased enzyme activity of MAOB has been reported in neurodegenerative disease models such as Parkinson's disease (Mallajosyula et al, 2008) and Alzheimer's disease (Chun et al, 2020;Ju et al, 2022). There may be steps in the process of astrocyte reactivation, and follow-up studies are needed to classify these steps (Escartin et al, 2021).…”
Section: Introductionmentioning
confidence: 99%